Person–Job Fit and Innovative Work Behavior: The Moderating Role of Perceived Organizational Support in the Context of Educational Management - Permatasari, Hartanti; Gunawan, Asep; Priyono, Dadang (Journal of Educational Management Research, 2025)
This study examines the effect of Person–Job Fit (PJF) on Innovative Work Behavior (IWB) with Perceived Organizational Support (POS) as a moderating variable, focusing on 100 employees of the National Narcotics Agency (BNN) in Karawang, Kuningan, and Cirebon. Using a quantitative survey design, data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The results show that PJF significantly and positively impacts IWB, indicating that better alignment between employee competencies and job requirements enhances innovative behavior. However, POS does not significantly moderate the PJF–IWB relationship. The model explains 80.5% of the variance in IWB (R² = 0.805). In educational management, these findings suggest that aligning employee competencies with job requirements can drive innovation among educators and staff, improving institutional performance. However, educational institutions should not rely solely on organizational support but also focus on ensuring a proper person-job fit. Future research could explore psychological mediators like creative self-efficacy to better understand innovation in education and other public sectors.